Exploratory Hand Movements Enhance the Liking Effect in Haptics. (September 2019) - Mitsuda, Takashi; Luo, Jiawei; Wang, Qiyan
When people choose between two items, they usually look at them alternately before deciding. The frequency and duration of contact are usually determined unconsciously. However, in a previous study, looking at one item for longer than the other increased participants' preference for the former, but only when they had to move their eyes to look at each item. This result implies that eye movements not only gather information but are also closely related to decision-making. By analogy, this study examines the relation between hand movements and haptic preference. When participants touched two handkerchiefs in a pre-determined order before choosing the one they preferred, the likelihood of choosing the more frequently touched handkerchief was greater than chance. Bias in the choice was greater with increased difference in the frequency of touching between the two handkerchiefs. It was also greater when participants moved their arm to touch the handkerchiefs, compared with when a machine carried the handkerchiefs to their hand. These results indicate that both the reaching movement for touching and the frequency of touching affect the preference judgment using haptics.